Investigation of associations between exposures to pesticides and testosterone levels in Thai farmers - Parinya Panuwet (2018)
© 2017 Taylor & Francis We conducted a cross-sectional study to assess the relationship between pesticide exposures and testosterone levels in 133 male Thai farmers. Urine and serum samples were collected concurrently from participants. Urine was analyzed for levels of specific and nonspecific metabolites of organophosphates (OPs), pyrethroids, select herbicides, and fungicides. Serum was analyzed for total and free testosterone. Linear regression analyses revealed significant negative relationships between total testosterone and the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) after controlling for covariates (eg, age, BMI, smoking status). Positive significant associations were found between some OP pesticides and total testosterone. Due to the small sample size and the observational nature of the study, future investigation is needed to confirm our results and to elucidate the biological mechanisms.